INOVASI LEKSIKAL BAHASA JAWA DI KABUPATEN PRINGSEWU LAMPUNG - Kurniawati, Desi (JURNAL PESONA, 2017)
The thesis is entitledâ The Lexical Innovation of Javanese in Pringsewu Regency Lampung: A Geolinguistics Studyâ. The research method used in this thesis is descriptive method. The method and technique of data gathering used is observation method, interview thecnique, and recording technique respectively. This research is carried out in 10 village from districts of Pringsewu Regency. The result of research shows that innovations are found, innovation include phonetic innovation, morphological innovation and lexical innovation. The phonetic innovation is raised as much as 50 words found 111 variants. The vocal form with the greatest number. Beside that, it also found the addition of replacement consonant, vocal, and indonesian loan word. The research showed 19 loan word.Â  In morfolofical found prefiks, sufiks, and reduplication word. 9 word raised in lexical innovation. Based of the map innovation happened at the same districts.